Toxicological studies of Caesalpinia sappan wood derived dye in Wister albino rats - G. Athinarayanana; A.J.A. Ranjitsingh; A. Usha Raja Nanthini; C. Padmalatha (Food Science and Human Wellness)
Natural dyes taken from the barks of the tree Caesalpinia sappan has been used in many consumer products. Hence it is imperative to test the toxicity of this dye. In the present study an investigation was conducted to find out the toxic effect of aqueous extract of the dye C. sappan in test animal Wister albino rats. Acute oral toxicity showed no clinical signs of toxicity and no mortality even at a dose level of 100–2000 mg/kg in 14 days observation period. When a dose level above 2500 mg/kg was given for 28 days, no death was noticed up to the dose level 5000 mg/kg body weight. The weight of the tested rats was not significantly reduced, when compared with the control group. The organ-body weight ratio of kidney, liver and abdomen did not change when compared to the control group in the observation period. The less toxicity of the dyes of C. sappan.